A cross sectional study of Infectious Bursal Disease and Newcastle Disease in poultry in Narsingdi district of Bangladesh - Islam, Shariful; Islam, Ariful; Moni, Shahnaj Parvin; Bari, Md. Saiful; Islam, Kamrul; Chakma, Shovon; Hossain, Md. Ershad; Siddiqe, Md. Zannatul Ferdous; Hoassain, Muhammad Belal; Chowdhury, Sharmin (Journal of Advanced Veterinary and Animal Research, 2017)
Objective: A cross sectional study was conducted to estimate the prevalence of Infectious Bursal Disease (IBD) and Newcastle Disease (ND) in poultry of Narsingdi district, Bangladesh. Materials and methods: Post mortem of a total of 208 dead birds were done for the diagnosis purpose. Different poultry species included in this study included broilers, layers, pigeon, duck etc. Results: Among the examined birds, 38% were found to be affected with IBD, and 11% were affected with ND. Age of the birds for both IBD (19.95; 95%CI: 16-23) and ND (122.23; 95%CI: 98.62-145.83); and flock size only for IBD (1317; 95%CI: 1175-1460) was found significantly associated. The chicks aging between 16-23 days and flock size between 1175-1460 were found to be the most susceptible group to IBD, and adult poultry (98.62-145.83 days old) was mostly susceptible to ND. Conclusion: IBD and ND are highly prevalent in the study area. Therefore, it is necessary to conduct effective control measures to reduce the prevalence of these diseases. This study can help in designing appropriate control measures considering risk factors of these diseases. http://doi.org/10.5455/javar.2016.c181